The Economy and the Constitution under the SNP, 2007–2016. Issue 1 (February 2016) - Kenealy, Daniel
Abstract : Since coming to power in 2007 the SNP have had to govern in two significant shadows. The first shadow is that of the financial crisis and the austerity programme of the UK's coalition government. The second shadow is that of ongoing constitutional change. This article considers both the economy and the constitution. It argues that, whilst the SNP in office have taken some measures to mitigate the effects of the crisis and the policies of the UK coalition government, they have introduced a number of policies that represent a triumph of style over substance. The article also raises questions about the additional powers that will be coming to Holyrood, especially regarding the practicalities of these powers and their ability to allow the Scottish Government to create a dramatically different welfare system to that in operation in the rest of the UK.